Photochemical Tissue Passivation Reduces Vein Graft Intimal Hyperplasia in a Swine Model of Arteriovenous Bypass Grafting - Goldstone, Robert N. (J Am Heart Assoc, 2016)
BACKGROUND: Bypass grafting remains the standard of care for coronary artery disease and severe lower extremity ischemia. Efficacy is limited by poor long‐term venous graft patency secondary to intimal hyperplasia (IH) caused by venous injury upon exposure to arterial pressure. We investigate whether photochemical tissue passivation (PTP) treatment of vein grafts modulates smooth muscle cell (SMC) proliferation and migration, and inhibits development of IH. METHODS AND RESULTS: PTP was performed at increasing fluences up to 120 J/cm(2) on porcine veins. Tensiometry performed to assess vessel elasticity/stiffness showed increased stiffness with increasing fluence until plateauing at 90 J/cm(2) (median, interquartile range [IQR]). At 90 J/cm(2), PTP‐treated vessels had a 10‐fold greater Young's modulus than untreated controls (954 [IQR, 2217] vs 99 kPa [IQR, 63]; P=0.03). Each pig received a PTP‐treated and untreated carotid artery venous interposition graft. At 4‐weeks, intimal/medial areas were assessed. PTP reduced the degree of IH by 66% and medial hypertrophy by 49%. Intimal area was 3.91 (IQR, 1.2) and 1.3 mm(2) (IQR, 0.97; P≤0.001) in untreated and PTP‐treated grafts, respectively. Medial area was 9.2 (IQR, 3.2) and 4.7 mm(2) (IQR, 2.0; P≤0.001) in untreated and PTP‐treated grafts, respectively. Immunohistochemistry was performed to assess alpha‐smooth muscle actin (SMA) and proliferating cell nuclear antigen (PCNA). Objectively, there were less SMA‐positive cells within the intima/media of PTP‐treated vessels than controls. There was an increase in PCNA‐positive cells within control vein grafts (18% [IQR, 5.3]) versus PTP‐treated vein grafts (5% [IQR, 0.9]; P=0.02). CONCLUSIONS: By strengthening vein grafts, PTP decreases SMC proliferation and migration, thereby reducing IH.